Improving of Creative Thinking Skill through Coding for all at Elementary Students - Saptajiah, Intan Saptajiah; Slameto, Slameto (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study explores the influence of coding for all on enhancing creative thinking skills among elementary students. 21st Century skills are essential abilities that help people work well with others, think of new ideas, speak clearly, and solve problems in this era world. It focuses in particular on the key soft skills competencies known as the "4Cs": creativity, critical thinking, collaboration, and communication. They are called "soft skills" because they are about working with people and ideas, not just using machines or following set rules. Creative thinking development is crucial for elementary school students as positively impacts their growth and learning process.According to Resnick et al. (2009), about the theory of coding for All, the aspiration to provide equal access and opportunity to the entire student population, regardless of their background or interests. This idea is based on the belief that coding for all is not only a technical skill, but also a powerful tool for stimulating creative thinking skill. The objective of this study is: 1. Identify Coding for all can increase the creativity of elementary students. 2. Improving of Creative Thinking Skill through Coding for all at Elementary Students. Following a search, a large amount of literature was found, and after selection, it included the following 5 sources about improving creative thinking skill by using coding for all. This study succeeded found 4 results from 5 article sources. The implication of this study is to provide socialization and innovation related to interactive learning media that supports the improvement of creative thinking in students with the aim of shaping student creativity and getting to know more intelligence in each student.